Meta-Testimonies: Theoretical Constructions from and on the Political Prison in the Southern Cone - Estrada Arellano, Sergio Iván (Revista de Historia Social y de las Mentalidades, 2023)
This research analized on the testimonial genre in Latin America, focusing specifically on how these are produced and developed. In this sense, the proposal of the research article refers to the possibility of considering a new type of testimony, around those texts’ intellectual production on the testimonies of the political prison in Latin America, developed by the victims of said processes, which can understood as meta-tes- timony, that is, an unconsidered form of testimony that theoretically addresses the testimony as a source and as an object of reflection, but which remains a testimony in itself. Well, it is part of a single reflection closely linked to the victim who writes and investigates it. To this end, the reflection focuses on two texts, Memorias Eclipsadas by the Chilean Jorge Montealegre, a political prisoner during the Pinochet military dictatorship, and Poder y DesaparicioÌn de Pilar Calveiro, an Argentine political prisoner during the Videla Dictatorship.